Interventions to improve infant and young child feeding practices in Ethiopia: a systematic review - Kingsley Emwinyore Agho; Felix Akpojene Ogbo; Andrew Page; Kingsley E Agho; Tanvir Abir; Kedir Y. Ahmed; Kedir Yimam Ahmed; Thierno Diallo; Osita E Ezeh; Osuagwu L Uchechukwu; Pramesh R Ghimire; Blessing Jaka Akombi; et al. (BMJ Open)
Objective In Ethiopia, despite the implementation of several interventions to improve infant and young child feeding (IYCF) practices, no published studies have highlighted the most effective IYCF interventions in the country. This systematic review investigated the impacts of various interventions on IYCF in Ethiopia.Source of information A systematic search was conducted on seven computerised bibliographic databases (Embase, ProQuest Central, Scopus, PsycINFO, Web of Science, MEDLINE/PubMed and CINAHL) to locate experimental or quasi-experimental studies published between the year 2000 and May 2021.Study eligibility criteria Interventional studies that measured IYCF indicators (early initiation of breast feeding (EIBF), exclusive breast feeding (EBF), the introduction of complementary foods, minimum dietary diversity (MDD), minimum meal frequency (MMF) and minimum acceptable diet) as outcome variables were included.Study appraisal and synthesis All included studies were examined for biases related to interventional studies (ie, selection bias, performance bias, attrition bias, detection bias and reporting bias). Author reports of effect size measures were used to narratively report the findings of each study.Results Of the 23 eligible studies, 14 studies were quasi-experimental and 9 studies were cluster randomised trials (CRTs). Eight quasi-experimental studies had a serious risk of bias, while two CRTs had a high risk of bias. Four studies for EBF and six studies for EIBF showed significant impacts of policy advocacy, health service strengthening, interpersonal communication, community mobilisation and mass media campaigns. Six studies for MDD and three studies for MMF indicated significant effects of community-level and health facility complementary feeding promotions on infants and young children. Interventions that delivered in combination increased the impacts in improving EIBF, MDD and MMF compared with a single intervention.Conclusion Our review showed that 12 out of 21 eligible studies that implemented in the form of community-level and health facility interventions improved EIBF, EBF, and/or MDD in Ethiopia.Protocol registration number PROSPERO, CRD42020155519.